INKUBASI DIGITAL TEKNOLOGI: UPAYA PELESTARIAN KESENIAN DAERAH GUNA PENGEMBANGAN KEARIFAN LOKAL BERBASIS BUDAYA DAN CULTURALPREUNERSHIP DI WILAYAH PEGUNUNGAN MERBABU - Kusuma, Dani; Santoso, Tri Nugroho Budi; Hardini, Agustina Tyas Asri; Maharani, Kristina; Elisabeth, Esra; Artha Sanjaya, Agustinus Victor; Mulyono, Bagus Tri; Adiningsih, Tiana Dwi (Jurnal Abdimas Bina Bangsa, 2024)
Desa Getasan, with its diverse cultural heritage and geographic potential, has strategic opportunities to develop a creative economy based on local cultural wealth. However, this potential has not been fully utilized due to the low interest of younger generations in preserving local arts and the limitations in cultural organization management and governance. This situation forms the basis for this community service project. The aim of this initiative is to preserve local arts and support the development of local wisdom through a cultural and entrepreneurial approach in Desa Getasan. The research is conducted from July to October 2024 in four stages: (1) planning stage, (2) program implementation stage, (3) product development stage, and (4) program evaluation stage. The outcomes from the training and mentoring of youth art performers include the development of an E-Cultural Catalog website, an organizational management handbook, a Culturalpreneurship Business Plan book, and a village art expo video, which have had a positive impact on the partners in terms of increased knowledge and skills. This community service activity fosters awareness of the importance of preserving cultural heritage in the form of local arts